2014
DOI: 10.1016/j.jbiomech.2014.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Increased initial cement–bone interlock correlates with reduced total knee arthroplasty micro-motion following in vivo service

Abstract: Aseptic loosening of cemented tibial components in total knee arthroplasty (TKA) has been related to inadequate cement penetration into the trabecular bone bed during implantation. Recent postmortem retrieval work has also shown there is loss of interlock between cement and bone by resorption of trabeculae at the interface. The goal of this study was to determine if TKAs with more initial interlock between cement and bone would maintain more interlock with in vivo service (in the face of resorbing trabeculae) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…For postmortem retrievals where there was less initial interlock and more time in service, there was more micromotion between the remaining interlocked trabeculae and cement. This is consistent with a previous study where we quantified the global micromotion for transverse sections of postmortem retrieved tibial components; implant sections with greater initial interlock had less micromotion after in vivo service . From a clinical perspective, attaining more initial interlock appears to result in cement‐bone interfaces that are better fixed with less micromotion.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For postmortem retrievals where there was less initial interlock and more time in service, there was more micromotion between the remaining interlocked trabeculae and cement. This is consistent with a previous study where we quantified the global micromotion for transverse sections of postmortem retrieved tibial components; implant sections with greater initial interlock had less micromotion after in vivo service . From a clinical perspective, attaining more initial interlock appears to result in cement‐bone interfaces that are better fixed with less micromotion.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with a previous study where we quantified the global micromotion for transverse sections of postmortem retrieved tibial components; implant sections with greater initial interlock had less micromotion after in vivo service. 17 From a clinical perspective, attaining more initial interlock appears to result in cement-bone interfaces that are better fixed with less micromotion. This would seem desirable from the perspective of minimize pumping of fluid or debris along the interface 18 and maintaining interface strength.…”
Section: Discussionmentioning
confidence: 99%
“…Bone-cement interface integrity has been identified as the critical element in the success and longevity of both hip and knee cemented replacements (Gardiner & Hozack, 1994;Stocks et al, 1995;Thanner et al, 1999;Zant et al, 2008;Wang et al, 2009;Tozzi et al, 2012;Goodheart et al, 2014;Howard et al, 2014;Miller et al, 2014Miller et al, , 2014b. Principal concerns regarding the performance of cemented fixation in the hip were related to fatigue damage accumulation in the cement mantle in femoral (Cristofolini et al, 2007;Race et al, 2003Race et al, , 2011 and acetabular (Heaton-Adegbile et al, 2006;Zant et al, 2007;Tong et al, 2008) components.…”
Section: Introductionmentioning
confidence: 99%
“…On the acetabular side the cracking in the cement mantle seems to be limited compared to the femoral counterpart and other failure mechanisms, such as debonding at the bone-cement interface, are mainly responsible for the implant loosening Wang et al, 2009;Tozzi et al, 2012). With regards to bone-cement fixation in the knee, a number of recent studies reported how the loss of interlock between bone and cement following in vivo service may eventually jeopardise the performance of both tibial Miller et al, 2014Miller et al, , 2014b and femoral (Howard et al, 2014) components over time. Goodheart et al (2014) also showed how such ex vivo loss of interlock resulted in a reduced strength of the bone-cement fixation in total knee arthroplasty (TKA).…”
Section: Introductionmentioning
confidence: 99%
“…A combination of functional micromechanics experiments and computational fluid dynamics modeling was used to determine cement‐bone micromotion and to estimate fluid flow in small gaps between trabeculae and cement in a rat knee replacement model. Not surprisingly, the measured micromotion magnitudes were much smaller than has been reported for comparable experiments performed on cemented human tibial components 10,17,18 . However, after normalizing to gap width, the scaled micromotion‐to‐gap width ratio was similar for the two species at the cement border and differed by a factor of two in interdigitated regions.…”
Section: Discussionmentioning
confidence: 55%